Utilizing Bioidentical Hormone as Efficacious and Safe Hormone - Jopy Wikana (Journal of Global Pharma Technology, 2019)
Background: The relative safety and efficacy of bioidentical hormone compared with synthetic version of hormone replacement therapy (HRT) is still the subject of debate. Some data suggest that bioidentical hormones have opposite physiological effects to synthetic hormones, which associated with lower risk of breast cancer and cardiovascular events. Nevertheless, there is still little evidence to support claims that bioidentical hormones are safer and more effective. Methods: Published papers were identified from PLOS, PubMed/MEDLINE, ProQuest, ScienceDirect, Google Scholar, and Elsevier (SCOPUS) databases, written in English, and fully accessible by reviewers, for studies enrolled postmenopausal women using bioidentical hormones vs. synthetic hormones as HRT. Results: A hundred and eighteen of 341 citations were reviewed. The results of this study found the disparities between bioidentical and synthetic hormones with respect to safety and efficacy. Bioidentical hormones have demonstrated effectiveness in addressing menopausal symptoms. Clinical data has indicated that bioidentical hormone, especially progesterone is associated with a diminished risk for breast cancer and cardiovascular disease, compared with commonly used synthetic versions. Conclusions: The use of bioidentical hormone therapy is well tolerated, provides symptom relief and can address the safer and more efficacious forms of HRT with respect to the lower risk for breast cancer and cardiovascular disease. Thus, bioidentical hormones remain the preferred method of HRT.Keywords: Progesterone, Estradiol, Synthetic progestins, Breast cancer, Cardiovascular disease,